2021
DOI: 10.3389/fnano.2021.693837
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Anti-Parasite Benzimidazole Drugs into Lipid-Coated Calcium Phosphate Nanoparticles to Efficiently Induce Skin Cancer Cell Apoptosis

Abstract: Benzimidazole (BMZ) family of anti-worm drugs has been now repurposed as anti-cancer drugs. However, offering a general reformulation method for these drugs is essential due to their hydrophobicity and low aqueous solubility. In this work, we developed a general approach to load typical BMZ drugs as tiny nanocrystals within lipid-coated calcium phosphate (LCP) nanoparticles. BMZ drug-loaded LCP nanoparticles increased their solubility in PBS by 100–200% and significantly enhanced the anti-cancer efficacy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Mentha longiflora / Mentha pulegium -LNPs and Zataria multiflora -LNPs reduced cell viabilities to under 10% and 13%, respectively [ 46 , 47 ]. Benzimidazole-LNPs induced cancer cell apoptosis, generated reactive oxygen species, and inhibited Bcl-2 expression in cancer cells while sparing toxicity among healthy HEK293T cells [ 48 ]. In vivo murine studies were additionally conducted with plumbagin-loaded lipid–polymer hybrid NPs (LPNP) and TMZ-LNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Mentha longiflora / Mentha pulegium -LNPs and Zataria multiflora -LNPs reduced cell viabilities to under 10% and 13%, respectively [ 46 , 47 ]. Benzimidazole-LNPs induced cancer cell apoptosis, generated reactive oxygen species, and inhibited Bcl-2 expression in cancer cells while sparing toxicity among healthy HEK293T cells [ 48 ]. In vivo murine studies were additionally conducted with plumbagin-loaded lipid–polymer hybrid NPs (LPNP) and TMZ-LNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that due to benzimidazole anthelmintic drug's poor solubility and low bioavailability, careful formulation strategy should be considered. 26 Although several formulation strategies were previously studied and proposed, 27,28 currently used benzimidazole anthelmintic drugs are orally administered for nonsystemic indications, but their pharmacokinetic parameters have not been fully reported. Based on fenbendazole and oxibendazole pharmacokinetic parameters, their increasing dose does not likely maintain the predose trough concentration (C trough ) for anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…Imidazole derivatives are a valuable class of nitrogen–containing heterocycles, whose synthesis and activities are always an attractive challenge among synthetic chemists [27–29] . Ketoconazole, miconazole and clotrimazole are imidazole derivatives and are widely used in the treatment of fungal infections [30–32] . Molecules containing imidazole ring are used to treat duodenal and gastric ulcers, gastroesophageal reflux disease, and associated symptoms such as heartburn and pain [33–35] .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Ketoconazole, miconazole and clotrimazole are imidazole derivatives and are widely used in the treatment of fungal infections. [30][31][32] Molecules containing imidazole ring are used to treat duodenal and gastric ulcers, gastroesophageal reflux disease, and associated symptoms such as heartburn and pain. [33][34][35] Figure 1 shows several examples of important pharmaceutical and bioactive compounds that have an imidazole ring in their structure.…”
Section: Introductionmentioning
confidence: 99%